ESTUDO SOBRE AS PRÁTICAS SEXUAIS PARA ALÉM DA DOR NA VISÃO DE PRATICANTES DE BDSM: STUDY ON SEXUAL PRACTICES BEYOND THE PAIN IN THE VIEW OF PRACTITIONERS OF BDSM - Ribeiro de Oliveira Santos, Adriana (2013)
This study resulted in job completion course guided by psychologist Ms. Vera Lucia Vaccari. The acronym BDSM consists of: Bondage, Discipline, Domination, Submission, Sadism and Masochism. There are many views on this universe, arising from psychology and psychiatry, which, with greater or lesser emphasis, often consider the practice a pathological perspective. OBJECTIVES: Raise the concepts related to pleasure and pain in practitioners of sadomasochism. MATERIALS AND METHODS: The research adopted a qualitative approach, based on a literature review and a field of work which included the collection of testimonials BDSM practitioners, raising the particularities of respondents considering the opinions, beliefs and significant in the words of survey participants by content analysis. DISCUSSION: The results point to a difference between the psychological and psychiatric vision and practitioners, who do not see the MS in a pathologizing perspective, but as a subculture. CONCLUSIONS: The psychology, the work with diversity, has the role of listening to the subject, on the grounds that there is healthy relationship of practitioners to your wishes with emphasis on exploring the various modes of sexual expression.project shows the positive impact of university involvement in the sex education of adolescents in the community, by providing also the academics, the experience of this work as part of university educations.